IMPROVEMENT OF DIAGNOSTICS AND TREATMENT OF SECONDARY CHRONIC PYELONEPHRITIS IN CHILDREN (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Despite the progress made in the diagnosis and treatment of nephropathies, in most 25% of patients they continue to progress, which leads to a change in the quality of life. Purpose of the study: to evaluate the complex treatment of chronic pyelonephritis in children. Materials and methods of research. The study involved 177 children with chronic pyelonephritis on the background of dysmetabolic disorders of the oxaluria type at the age of 4 to 15 years. Results. More pronounced changes in the cytokine urine profile in patients were revealed on the background of the use of RLAT in combination with vitamin A (group II). Our study showed that the "average" concentration of IL-1, IL-6, IL-8 in urine in children of the 2nd group after treatment with 4th scheme had a more positive downward trend, compared to group 1. After treatment of group II of patients, the level of IL-10 had a relatively high tendency toward normalization (P1 0.01), compared to group 1 (P1> 0.1). Conclusions. 1. In the period of exacerbation of chronic (oxalate) pyelonephritis, damages to partial functions of the kidneys were noted in patients: a decrease in the glomerular filtration rate, osmolarity of urine, daily diuresis; immune disorders: a significant decrease in IL-10 and an increase in IL-1, IL-6, IL-8 in urine.